TOXICOLOGICAL PROFILE ON AYAPODI ELAGAM - A SIDDHA HERBOMINERAL FORMULATION IN WISTER ALBINO RATS - A, *Kalaivani; K, Jeevaraj; P, Shanmugapriya; R, Madhavan (International Journal of Ayurveda and Pharma Research, 2019)
Ayapodi Elagam (A.E) was used in Siddha system of medicine for many years to treat Pandu (Anemia). This medicine contains Nellikai, Keezhanelli, Karisalai and Ayam. These herbs are helps to improve the blood to correct the anemia. This study was carried out to evaluate the acute and chronic toxic effect on Ayapodi Elagam and to determine the LD50. The toxicity study was done as per the guidelines of world health organization (WHO) guideline. As the herbs and Ayam were used for treating anemia by traditional practitioners for years together, the toxicity study was also proposed to study in both sexes. In acute study the animals were divided into two groups A.E was administered at 5000mg/kg orally and animals were observed for toxic sign at 0,5,1,4,24 hour and for 14 days. In chronic toxicity study A.E was administered at 450,900 and 1800 mg/kg body weight/day to 3 groups of animal, respectively. The distilled water was administered to control animals. The result showed that the acute toxicity study of A.E. at the dose level of 5000mg/kg does not produce any toxic sign and mortality among the experimental groups and the LD50 value of the drug was found to be more than 5000mg/kg bodyweight. The weight of rats, wellness parameters, mortality, hematological parameters, biochemical parameters and histological analysis of all vital organs were observed to know the chronic toxic effect of the drug. All the parameters of the study do not show the any significant chances between the control and experimental groups.